Mechanics of growing tumors: impact of modeling assumptions and boundary conditions on reliability of numerical results. Issue 1 (21st October 2015) - Sciumè, Giuseppe; Schrefler, Bernhard A.; Santagiuliana, Raffaella; Zavarise, Giorgio
Abstract A recent computational model for tumor growth is presented. The mathematical model, based on thermodynamically constrained averaging theory (TCAT), is shortly summarized in the first part; then the attention is focused on modeling hypothesis and their impact on numerical results. Perspectives for future developments of the presented multiphase model are outlined at the end of the paper. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)